SOCIB integrated multi-platform ocean observing and forecasting: from ocean data to sector-focused delivery of products and services. (20th November 2019) - Heslop, Emma; Tintoré, Joaquín; Rotllan, Paz; Álvarez-Berastegui, Diego; Fontera, Biel; Mourre, Baptiste; Gómez-Pujol, Lluís; March, David; Casas, Benjamin; Nolan, Glenn; Durand, Dominique
ABSTRACT: In the last 10 years, new monitoring and modelling technologies have emerged allowing real-time observation and forecasting of the coastal ocean at regional and local scales. These technologies are at the core of multi-platform integrated observing and forecasting systems, such as the Balearic Islands Coastal Ocean Observing and Forecasting System (SOCIB). New capabilities to characterise the state of the ocean and its variability at finer spatial and temporal scales are emerging, supporting science and products for society. SOCIB has a well-defined mission to deliver ocean observing for the benefit of science and society. From initiation in 2010, SOCIB has provided high-quality, free and open data. In order to increase our utility, we developed a Products and Services Strategy rooted in business best practice. Ten sectors – groups of users with common data needs – were identified, for which SOCIB has information and knowledge of high value. Dedicated products were developed in cooperation with the end-users: beach lifeguards/managers and sustainable marine resources managers. We illustrate an integrative approach, combining business concepts with collaborative software development methodologies and ocean observing science, to turn ocean observations and forecasts into products and services, with benefits for society in the sustainable blue economy era.